AN OVERVIEW OF THE RELATIONS WITHIN THE IRON TRIANGLE ON A SAMPLE OF CONSTRUCTION PROJECTS IN CROATIA - Tijanić Štrok, Ksenija (Journal of Applied Engineering Science, 2025)
The construction project’s success generally implies completion within the planned deadline and budget and satisfactory quality performance. These three project performance parameters form the basic system of measuring its success - the iron triangle of project management. Unfortunately, construction projects often fail to meet the defined success parameters, one or more. The focus of this paper is the territory of Croatia, for which it was noticed that no comprehensive studies analyze the construction projects’ success in terms of all three iron triangle parameters. This paper aimed to observe an extensive database of projects from Croatia, analyze their success in terms of time, costs, and construction quality, and determine the mutual relations between those three parameters. Based on a database of 49 construction projects, it was determined that a significant number of projects (46.94%) were not satisfactory regarding time and cost success. At the same time, problematic quality performance was less common (20.41%). Statistically significant correlations were established between the performance of time and cost. Developing reliable mathematical models for predicting real construction time and cost is also possible. As for the construction quality, the problem of its presentation and assessment has been established, and no statistically significant results have been determined by observing it. These results indicate the need for further research, primarily regarding the project performance quality. The overall results emphasize the importance of comprehensive, systematic and timely construction project management, primarily during the planning and execution phases, to achieve its goals.